EXPERIENCE WITH THE OBJECTIVE STRUCTURED CLINICAL EXAMINATION AS A TOOL FOR STUDENT'S ASSESSMENT IN THE DEPARTMENT OF SURGERY IN THE COLLEGE OF MEDICINE, ALNAHRAIN UNIVERSITY (Iraqi Journal of Medical Sciences, 2004)
Objectives: The objective of this study is to compare the student's  performance in the objective structured clinical examination (OSCE) in surgery to the results of multiple choice questions and to the traditional clinical examination and to find out that OSCE is more valid , reliable , practical than the traditional clinical examination and similar to MCQs .  Subjects & Method: All 47 sixth-year medical students of the Medical College, Al-Nahrain University in the academic year 2001-2002 were enrolled in this study. There were 3 data sets from the result of OSCE, MCQs, and the traditional clinical examination. By using paired t-test (p) and the correlation coefficient of Pearson (r) the results were compared with each other.  Results: Analysis of the results of the three examinations revealed high correlation between OSCE and MCQs and a significant difference was noted between OSCE and the traditional clinical examination. Conclusion: The result of this study support the previously reported finding of the low correlations between OSCE and the traditional clinical examination .The OSCE is similar to MCQs in its validity; reliability and it cover a wide range of knowledge and clinical skills and minimize the effect of both the examiners and the patients on the result of the examination.                                                       Keywords: Objective structured clinical examination OSCE, Multiple-choice questions MCQs, Traditional clinical examination. Iraqi J Med Sci, 2004; Vol. 3 (1): 55-58